Disruptive Cooperation in Digital Health - Ranck, Jody (Springer International Publishing : Imprint: Springer, 2016)
This clear-sighted volume introduces the concept of "disruptive cooperation"- transformative partnerships between the health and technology sectors to eliminate widespread healthcare problems such as inequities, waste, and inappropriate care. Emphasizing the most pressing issues of a world growing older with long-term chronic illness, it unveils a new framework for personalized, integrative service based in mobile technologies. Coverage analyzes social aspects of illness and health, clinically robust uses of health data, and wireless and wearable applications in intervention, prevention, and health promotion. And case studies from digital health innovators illustrate opportunities for coordinating the service delivery, business, research/science, and policy sectors to promote healthier aging worldwide. Included among the topics: Cooperation in aging services technologies The quantified self, wearables, and the tracking revolution Smart healthy cities: public-private partnerships Beyond silos to data analytics for population health Cooperation for building secure standards for health data Peer-to-peer platforms for physicians in underserved areas: a human rights approach to social media in medicine Disruptive Cooperation in Digital Health will energize digital health and healthcare professionals in both non-profit and for-profit settings. Policymakers and public health professionals with an interest in innovation policy should find it an inspiring ideabook. .